The vertical cooperation and pricing strategies of electric vehicle supply chain under brand competition. (February 2021) - Fan, Zhi-Ping; Huang, Shuai; Wang, Xiaohuan
Highlights: Cooperation and competition in electric vehicle supply chain are considered. Optimal pricing strategies are obtained under three cooperation strategies. The impacts of brand effect on electric vehicle supply chain are investigated. Useful managerial insights for supply chain partners are given. Abstract: This paper considers an electric vehicle supply chain composed of a battery supplier, a well-known brand manufacturer (Manufacturer A) and an ordinary brand manufacturer (Manufacturer B). Three strategies are studied, namely, the noncooperative strategy (hereafter "Strategy N"), the cooperation strategy between the battery supplier and Manufacturer A (hereafter "Strategy S-A"), and the cooperation strategy between the battery supplier and Manufacturer B (hereafter "Strategy S-B"). Under these strategies, we investigate the optimal sales prices of the battery and electric vehicles of the two brands. We then analyze the impacts of brand effect on the demands of the two electric vehicles and the profits of all enterprises. The theoretical and numerical analyses present some valuable findings. First, Strategy S-A improves the demand and the profit of Manufacturer A, but reduces the demand and the profit of Manufacturer B; inversely, Strategy S-B increases the demand and profit of Manufacturer B, but decreases the demand and profit of Manufacturer A. Under Strategy S-B, the total demand for the two brands of electric vehicles is the largest. Second, Strategy S-A can intensify price competition, while Strategy S-B can weaken price competition between the two manufacturers. Third, when the degree of brand difference is relatively low, or the ratio of Manufacturer A's bargaining power to Manufacturer B's bargaining power is high, the battery supplier's profit under Strategy S-B is the highest; otherwise, the battery supplier can obtain the highest profit from Strategy S-A. Finally, vertical cooperation strategies do not always improve the overall profitability of the supply chain.